Sarthaks Test
0 votes
42 views
in Mathematics by (15.0k points)

Solve the question   ;

(i) x4 − (x − z)4

(ii) a4 − 2a2b2 + b4

1 Answer

0 votes
by (24.8k points)
selected by
 
Best answer

(i) x4 − (x − z)4 = (x2)2 − [(x − z)2]2

= [x2 − (x − z)2] [x2 + (x − z)2]

= [x − (x − z)] [x + (x − z)] [x2 + (x − z)2]

= z(2x − z) [x2 + x2 − 2xz + z2]

= z(2x − z) (2x2 − 2xz + z2)

(ii) a4 − 2a2b2 + b4 

= (a2)2 − 2 (a2) (b2) + (b2)2

= (a2 − b2)2

= [(a − b) (a + b)]2

= (a − b)2 (a + b)2

Welcome to Sarthaks eConnect: A unique platform where students can interact with teachers/experts/students to get solutions to their queries. Students (upto class 10+2) preparing for All Government Exams, CBSE Board Exam, ICSE Board Exam, State Board Exam, JEE (Mains+Advance) and NEET can ask questions from any subject and get quick answers by subject teachers/ experts/mentors/students.

Categories

...